Mobile base station with conformational selections for the network maintenance in wireless multihop infrastructure. Issue 5 (24th November 2016) - Teng, Rui; Li, Huan‐Bang; Miura, Ryu
Abstract: Wireless multihop infrastructure (WMI) networks can provide essential support for information exchange and the Internet access, particularly during emergencies and in smart cities. However, limited network resources during emergencies may result in node energy depletion and network disconnection, leading to service failures to users in the WMI network. This paper aims to use mobile base stations (MBSs) to automatically form paths and spontaneously maintain network availability as a connected infrastructure. The problems to deal with are the limited information and resources for MBS to quickly construct efficient connections in a WMI network. We propose a bio‐inspired approach, which enables MBS to interact with the network based on insights from conformational selections in enzyme‐substrate binding. In analogy to selective binding of enzyme‐substrates, the proposed MBS approach uses selective pauses based on the traffic status of selective packet forwarding at appropriate positions, at which MBS is capable of sustaining WMI connectivity. The proposed MBS approach reduces energy consumption of base stations that have energy constraints and heavy traffic to handle, and it improves WMI network availability. Evaluation using packet‐level simulation reveals that the proposed MBS approach achieves up to 40% improvement for the availability of network as a full connected infrastructure. Abstract : This paper aims to utilize mobile base stations (MBS) to automatically form paths and spontaneously maintain network availability as a connected infrastructure. We propose a bio‐inspired approach, which enables MBS to interact with the network based on insights from conformational selections in enzyme‐substrate binding. A notable feature of the proposed approach is that chains of selective pause extensions are automatically issued to sustain network connectivity according to the traffic status at MBS.